Economic Analysis for Using Solar Energy Implementation to Support the Development of Nusantara Capital - Muhammad Syamil Fadlillah; Erma Suryani; Rahmatika Jagad Pramundito (Institute for Research and Community Service (LPPM), Universitas Malikussaleh, Indonesia, 2024)
The dynamic simulation model for economic analysis of solar energy in the new Indonesia's capital named IKN is a computer system designed to evaluate the viability of solar energy as a power source in the new capital being developed in East Kalimantan. The model aims to assess the economic feasibility of solar energy implementation, addressing cost-effectiveness. Strategies include policy enforcement, land optimization, and population growth impacts. The model's validation showed an error rate ‰¤ 5% and error variance ‰¤ 30%, confirming its accuracy. Scenario simulations (most likely, pessimistic, and optimistic) forecasted varying returns on investment (ROI), indicating solar energy's profitability under different conditions. The optimistic scenario predicted the highest ROI of 42% by 2045, with a break-even point by 2026.